2019
DOI: 10.1016/j.jses.2019.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Total shoulder arthroplasty with nonspherical humeral head and inlay glenoid replacement: clinical results comparing concentric and nonconcentric glenoid stages in primary shoulder arthritis

Abstract: BackgroundGlenoid morphology can influence the outcomes of total shoulder arthroplasty. This study examines the results of a new technique according to preoperative glenoid staging. We hypothesized that there would be no statistically significant difference in outcomes between Levine concentric (Walch A) and Levine nonconcentric (Walch B) glenoids treated for primary glenohumeral arthritis using nonspherical humeral head and inlay glenoid replacement.MethodsThis retrospective case series included 31 shoulders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 43 publications
0
44
0
Order By: Relevance
“…These range of motion improvements are clinically comparable to findings seen at 2 years of follow-up with other modern stemless and stemmed shoulder arthroplasty systems. 6,13,15,35,55 However, without a direct comparison group, we cannot comment on if the elliptical humeral head component used in this patient cohort afforded any clinical benefit compared with other prosthetic designs.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…These range of motion improvements are clinically comparable to findings seen at 2 years of follow-up with other modern stemless and stemmed shoulder arthroplasty systems. 6,13,15,35,55 However, without a direct comparison group, we cannot comment on if the elliptical humeral head component used in this patient cohort afforded any clinical benefit compared with other prosthetic designs.…”
Section: Discussionmentioning
confidence: 94%
“…Egger et al 15 reported a series of 31 shoulders that underwent TSA using a nonspherical, ovoid-shaped humerus resurfacing implant and an inlay glenoid in a singlesurgeon series. Similar positive results were found.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations